A research-informed dialogic-teaching approach to early secondary school mathematics and science: the pedagogical design and field trial of the epiSTEMe intervention. Issue 1 (1st January 2017) - Ruthven, Kenneth; Mercer, Neil; Taber, Keith S.; Guardia, Paula; Hofmann, Riikka; Ilie, Sonia; Luthman, Stefanie; Riga, Fran
Abstract: The Effecting Principled Improvement in STEM Education [ epiSTEMe ] project undertook pedagogical research aimed at improving pupil engagement and learning in early secondary school physical science and mathematics. Using principles identified as effective in the research literature and drawing on a range of existing pedagogical resources, the project designed and trialled a classroom intervention, with associated professional development, in a form intended to be suited to implementation at scale. The most distinctive feature of the epiSTEMe pedagogical approach is its inclusion of a component of dialogic teaching. Aimed at the first year of secondary education in English schools (covering ages 11–12), the epiSTEMe intervention consists of a short introductory module designed to prepare classes for this dialogic teaching component, and topic modules which employ the epiSTEMe pedagogical approach to cover two curricular topics in each of science and mathematics. A field trial was conducted over the 2010/2011 school year in 25 volunteer schools, randomly assigned to intervention and control groups. Within the intervention group, observation of lessons indicated that the level of dialogic teaching was higher for one of the topic modules than others. Evaluation focused on the effectiveness of the topic modules, each trialled in more than 10 classes containing a total of over 300 pupils, and compared with a group of similar composition. Overall, at this first implementation, learning gains under the epiSTEMe intervention were no greater, although for individual topic modules the effects ranged from small negative to small positive. No difference was found between intervention and control groups either in the opinion of pupils about their classroom experience or in changes in their attitude towards subjects.